Lebein, a Snake Venom Disintegrin, Induces Apoptosis in Human Melanoma Cells - Manel B. Hammouda; María F. Montenegro; Luis Sánchez-del-Campo; Ons Zakraoui; Zohra Aloui; Ichrak Riahi-Chebbi; Habib Karoui; José Neptuno Rodríguez-López; Khadija Essafi-Benkhadir (Toxins, 2016)
Melanoma, the most threatening form of skin cancer, has a very poor prognosis and is characterized by its very invasive and chemoresistant properties. Despite the recent promising news from the field of immunotherapy, there is an urgent need for new therapeutic approaches that are free of resistance mechanisms and side effects. Anti-neoplasic properties have been highlighted for different disintegrins from snake venom including Lebein; however, the exact effect of Lebein on melanoma has not yet been defined. In this study, we showed that Lebein blocks melanoma cell proliferation and induces a more differentiated phenotype with inhibition of extracellular signal-regulated kinase (ERK) phosphorylation and microphthalmia-associated transcription factor (MITF) overexpression. Melanoma cells became detached but were less invasive with upregulation of E-cadherin after Lebein exposure. Lebein induced a caspase-independent apoptotic program with apoptosis inducing factor (AIF), BCL-2-associated X protein (BAX) and Bim overexpression together with downregulation of B-cell lymphoma-2 (BCL-2). It generated a distinct response in reactive oxygen species (ROS) generation and p53 levels depending on the p53 cell line status (wild type or mutant). Therefore, we propose Lebein as a new candidate for development of potential therapies for melanoma.